Marked Disparities in COVID-19 Vaccination among US Children and Adolescents by Racial/Ethnic, Socioeconomic, Geographic, and Health Characteristics, United States, December 2021 - April 2022 - Gopal K Singh; Hyunjung Lee; Romuladus E. Azuine (Global Health and Education Projects, Inc., 2022)
Background: The COVID-19 pandemic has had a substantial adverse impact on the health and well-being of populations in the United States (US) and globally. Although COVID-19 vaccine disparities among US adults aged ≥18 years are well documented, COVID-19 vaccination inequalities among US children are not well studied. Using the recent nationally representative data, we examine disparities in COVID-19 vaccination among US children aged 5-17 years by a wide range of social determinants and parental characteristics. Methods: Using the US Census Bureau's Household Pulse Survey from December 1, 2021 to April 11, 2022 (N=86,335), disparities in child vaccination rates by race/ethnicity, socioeconomic status, health insurance, parental vaccination status, parental COVID-19 diagnosis, and metropolitan area were modeled by multivariate logistic regression. Results: During December 2021-April 2022, an estimated 40.1 million or 57.2% of US children aged 5-17 received COVID-19 vaccination. Vaccination rates were lowest among children of parents aged 25-34 (34.9%) and highest among children of parents aged 45-54 (69.2%). Children of non-Hispanic Black parents, divorced/separated and single individuals, parents with lower education and household income levels, renters, not-employed parents, the uninsured, and parents without COVID-19 vaccination or with COVID-19 diagnoses had significantly lower rates of vaccination. Controlling for covariates, Asian and Hispanic children aged 5-17 had 134% and 47% higher odds of receiving vaccination than their non-Hispanic White counterparts. Children of parents with a high school education had 47% lower adjusted odds of receiving vaccination than children of parents with a master's degree or higher. Children with annual household income <$25,000 had 48% lower adjusted odds of vaccination than those with income ≥$200,000. Although vaccination rates were higher among children aged 12-17 than among children aged 5-11, sociodemographic patterns in vaccination rates were similar. Parental vaccination status was the strongest predictor of children's vaccination status Vaccination rates for children aged 5-17 ranged from 49.6% in Atlanta, Georgia to 82.6% in San Francisco, California. Conclusion and Global Health Implications: Ethnic minorities, socioeconomically-disadvantaged children, uninsured children, and children of parents without COVID-19 vaccination or with COVID-19 diagnoses had significantly lower vaccination rates. Equitable vaccination coverage among children and adolescents is critical to reducing inequities in COVID-19 health outcomes in the US and globally.   Copyright © 2022 Singh et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0.